A Comparison of Functional Behavioral Assessment and Functional Analysis Methodology among Students with Mild Disabilities. (November 2015) - Lewis, Timothy J.; Mitchell, Barbara S.; Harvey, Kristin; Green, Ambra; Mckenzie, Jennifer
Functional behavioral assessment (FBA) and functional analyses (FA) are grounded in the applied behavior analysis principle that posits problem behavior is functionally related to the environment in which it occurs and is maintained by either providing access to reinforcing outcomes or allowing the individual to avoid or escape that which they find aversive. Previous research has pointed to the limitations across FBA methodologies in comparison to the direct experimental trials used in FA. The purpose of this study was to evaluate the degree to which hypotheses generated by common FBA strategies (i.e., interview, rating scale, and direct observation) match hypotheses generated through FA trials. Results of a multiphase descriptive study indicated that traditional school personnel with behavioral expertise were able to generate FBA hypotheses that were later confirmed by independent review and largely aligned with FA outcomes. The impact of the findings for the field and implications for future research and practice are discussed.